2008
DOI: 10.1136/bjsm.2008.050807
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation of splenic enlargement in athletes with acute infectious mononucleosis

Abstract: The majority of athletes with IM experience a moderate degree of splenomegaly. Peak splenic enlargement occurs within 2 weeks from the time of symptom onset in most cases, but may extend to 3.5 weeks. The rate of splenic enlargement appears to be predictable for an individual who develops IM. Ultrasonographic data further show that splenomegaly associated with acute IM infection resolves within 4-6 weeks of symptom onset in the majority of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 5 publications
3
32
0
Order By: Relevance
“…Most cases of splenomegaly had resolved by 4-6 weeks and there was a predictable rate of splenic regression of approximately 1% each day after reaching peak enlargement. 17 Similar results were reported in another paper, with normalisation of spleens at one month in 84% of participants. w62 One study recommended that athletes wanting to return to contact sport at 3-4 weeks should have an ultrasound examination to ensure that the spleen had returned to normal size.…”
Section: When Is It Safe To Return To Sports?supporting
confidence: 88%
“…Most cases of splenomegaly had resolved by 4-6 weeks and there was a predictable rate of splenic regression of approximately 1% each day after reaching peak enlargement. 17 Similar results were reported in another paper, with normalisation of spleens at one month in 84% of participants. w62 One study recommended that athletes wanting to return to contact sport at 3-4 weeks should have an ultrasound examination to ensure that the spleen had returned to normal size.…”
Section: When Is It Safe To Return To Sports?supporting
confidence: 88%
“…33,45 In ultrasound studies, peak spleen size is typically noted within the first 2 weeks of illness, but may extend to 3.5 weeks. 18 The majority of spleen injuries occur within the first 21 days of illness and are exceedingly rare at >28 days. 21,26,43 Fortunately, splenic rupture is rare, occurring in <0.5% of those with IM, but its consequences can be severe.…”
Section: Return-to-play Considerationsmentioning
confidence: 99%
“…In a study similar to ours published in 2008, Hosey at al investigated the role of weekly ultrasonography in determining when 20 athletes with infectious mononucleosis could return to contact sports; these assessments continued until splenomegaly resolved. 17 Th e authors observed a mean increase in splenic length of 36-month period from August 2004 through July 2007. We identifi ed all patients who had been admitted to our hospital's otolaryngology unit with acute tonsillitis.…”
Section: Discussionmentioning
confidence: 94%